KARAKTERISTIK PAPAN KOMPOSIT BERBAHAN KOMBINASI SERAT RAMI DAN SERAT BATANG PISANG - Hidayatullah, Zul; Suparno, Suparno; Nadhiroh, Nuraini (Jurnal Riset Fisika Edukasi dan Sains, 2020)
This study aims to determine the feasibility of a composite board made of hemp fiber and banana stem fiber with Poly Vinyl Acetate (PVAc). Making the composite board begins with the preparation, drying, weighing the raw materials according to the weight ratio, mixing, pressing and cutting the finished composite board according to the size required in the test standard. Composite board characteristic testing includes: moisture content, thickness swelling, density, flexural strength and tensile strength of the composite papn. The test results on the composite showed that the more the value of the banana stem fiber used as a combination for the hemp fiber, the more the feasibility value of the composite board did not meet SNI standards. However, for the bending test, all categories of fiber combinations were not feasible because the sample specimens were not stiff due to PVAc which only functions as an adhesive (not a reinforcement).